The Development of Plastic Concrete Mix with Recycled Plastic (HDPE) in Concrete Production for Flat Roof of Sustainable Building - Huan, Kok Wei; bin Abdul Rahman, Mohd Fahmi (Progress in Engineering Application and Technology, 2021)
Flat roof is the common roof design in modern building. Plastic waste is the main pollution in the environment. Recycling and reuse of plastic is method to reduce pollution. This study focused on the development of plastic concrete with the addition of High Density Polyethene (HDPE). The aim of the study is to investigate the optimum plastic concrete mix by determine the properties of compressive strength, thermal conductivity and water absorption. The samples of plastic cement ratio of 1:50 (2%), 1:25 (4%) and 3:50 (6%) are prepared and tested. The sample of 2% plastic-cement percentage achieved the compressive strength requirement of Grade 20 in 7days and 28days. The compressive strength reduced with addition of HDPE. The 4% plastic-cement percentage sample had the greatest reduction in thermal conductivity about 12%. Water absorption of plastic concrete had an increasing trend with addition of HDPE. The 2% plastic-cement percentage sample is proposed to be the optimum plastic concrete mix as flat roof concrete. The addition of HDPE in concrete mix affect the properties of concrete.